Identity-Based Federalism: Ethiopia’s Crisis and Nepal’s Future - Magar, Deepak Pun (International Research Journal of MMC, 2026)
Identity-based federalism has been widely promoted as a mechanism for managing ethnic diversity, political inclusion, and historical marginalization in multiethnic societies. This manuscript examines identity-based federalism through a comparative analysis of the ongoing federal crisis in Ethiopia and its relevance for the federal future of Nepal. This study, based on secondary sources, explores how the institutionalization of identity within federal structures can empower marginalized groups. It can generate new forms of political conflict. Methodologically, this research adopted both a qualitative and comparative approach based entirely on secondary data, including scholarly literature, constitutional texts, and policy analyses on federalism, ethnicity, and conflict in Ethiopia and Nepal, dating from 1982 till 2026. The findings indicate that Ethiopia’s ethnic federal model, while initially addressing demands for recognition and self-governance, has contributed to intense ethnic mobilization, governance failure, and challenges to state unity. The study further shows that weak institutions, elite manipulation of identity, and contradictions between constitutional design and political practice have played a decisive role in escalating conflict. In contrast, Nepal’s territorially based federal system offers greater flexibility but remains vulnerable to identity-based political pressures. The study concludes that the Ethiopian experience provides important lessons for Nepal, which emphasize the need for strong democratic institutions, cooperative federalism, and inclusive civic identities to ensure that federalism serves as a framework for stability rather than division in multi-ethnic states.